Managing the Millennials, 2nd Edition - Espinoza, Chip; Ukleja, Mick (Ascent Audio, 2019)
The Builders, Baby Boomers, Generation X, and Millennials-all make up workforces in every type of industry all over the world. The generational gaps are numerous and distinctly different between each age group, and Millennials have gotten a reputation for being particularly unique and often challenging. In this updated and expanded Second Edition of the popular guidebook Managing the Millennials, you'll see how Millennial traits are the same around the globe. In fact, Millennials are more alike than any other generation before them due in large part to rapid advances in technology that let us share more experiences together. These same rapid advances are also redefining the fundamental ways businesses operate, and this revised edition includes the international perspective today's leadership needs to attract and retain these high-performing workers. With fresh research and new real-world examples, the powerhouse authorial team reexamines the differences between how different generations work today in businesses around the world, with insightful exploration into what makes the Millennial generation so different from the ones that came before. The authors reveal nine specific points of tension commonly arising from clashing value systems among generations and prescribe nine proven solutions to resolve conflict and build communication.